Real-World Data on NGS Diagnostics: a survey from the Italian Society of Pathology (SIAPeC) NGS Network - Marchetti, Antonio; Barbareschi, Mattia; Barberis, Massimo; Buglioni, Simonetta; Buttitta, Fiamma; Fassan, Matteo; Fontanini, Gabriella; Marchiò, Caterina; Papotti, Mauro; Pruneri, Giancarlo; Scarpa, Aldo; Stanta, Giorgio; et al. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
Next Generation Sequencing (NGS) is increasingly used in diagnostic centers for the assessment of genomic alterations to select patients for precision oncology. The Italian Society of Anatomic Pathology and Diagnostic Cytopathology (SIAPEC) through the Molecular Pathology and Predictive Medicine Study Group (PMMP) has been following the progressive development of centers that have adopted NGS technology in diagnostics over time. In July 2017, a study network on massive parallel sequencing was activated in Italy and recognized as the NGS SIAPeC National Network by the SIAPeC Scientific Society Board. Since then, activities have been implemented within the network that provide for alignment of laboratories through diagnostic concordance analysis and monitoring of centers adhering to the Network. Recently, considering the growing need for extended genomic analyses, the PMMP distributed a national survey to assess activities related to the use of genomic diagnostics in oncology within the NGS SIAPEC National Network. Thirty centers participated in the survey. Eighty percent of the centers are laboratories within Pathology Departments. The distribution of laboratories in the country, the diagnostic laboratory/population ratio, the staff dedicated, the type and number of sequencing and mechatronics platforms available, the genomic panels utilized, and the type and number of diagnostic tests carried out in the last year in each center, are reported. The centers were also asked whether they participated in a multidisciplinary Molecular Tumor Board (MTB) for management of patients. Thirty percent of the centers had a MTB that was ratified by regional decree. The professionals most frequently involved in the core team of the MTB are the pathologist, oncologist, molecular biologist, geneticist, pharmacologist, and bioinformatician. The data from this survey indicate that NGS diagnostics in Italy is still heterogeneous in terms of geographical distribution and the characteristics of laboratories and diagnostic test performed. The implementation of activities that favors harmonization, the logistics and the convergence of biological material in reference centers for molecular analyses is a priority for the development of a functional laboratory network.